On musical patronage: popular music, oil capitalism, and state politics in Equatorial Guinea - Infante Amate, P (2021)
This doctoral thesis examines the centrality of the state in the constitution of the popular music economy in Equatorial Guinea. It examines transformations and continuities in music production, circulation, and consumption as they have been shaped by the introduction of digital technologies and the Central African micro-state’s growing dependence on the export of fossil fuels. The spectacular oil boom of the last quarter century has consolidated the already-authoritarian rule of Teodoro Obiang Nguema, who stands today as one of the longest-serving heads of state in the world. From within a highly politicised social sphere, popular music emerges as a privileged medium, employed by the petro-elites to accumulate prestige and by musicians to negotiate their relations with the state and to gain access to (unequally distributed) oil revenues.